An antioxidant response is involved in resistance of Giardia duodenalis to albendazole - Argüello-García, Raúl; Cruz-Soto, Maricela; González-Trejo, Rolando; Paz-Maldonado, Luz María Teresita; Bazán-Tejeda, María Luisa; Mendoza-Hernández, Guillermo; Ortega-Pierres, M. Guadalupe (Frontiers in Microbiology, 2015)
Albendazole (ABZ) is a therapeutic benzimidazole used to treat giardiasis that targets β-tubulin. However the molecular bases of ABZ resistance in Giardia duodenalis are not understood because β-tubulin in ABZ-resistant clones lacks mutations explaining drug resistance. In previous work we compared ABZ-resistant (1.35, 8 and 250 M) and ABZ-susceptible clones by proteomic analysis and eight proteins involved in energy metabolism, cytoskeleton dynamics and antioxidant response were found as differentially expressed among the clones. Since ABZ is converted into sulphoxide (ABZ-SO) and sulphone (ABZ-SOO) metabolites we measured the levels of these metabolites, the antioxidant enzymes and free thiols in the susceptible and resistant clones. Production of reactive oxygen species (ROS) and levels of ABZ-SO/ABZ-SOO induced by ABZ were determined by fluorescein diacetate-based fluorescence and liquid chromatography respectively. The mRNA and protein levels of antioxidant enzymes (NADH oxidase, peroxiredoxin 1a, superoxide dismutase and flavodiiron protein) in these clones were determined by RT-PCR and proteomic analysis. The intracellular sulfhydryl (R-SH) pool was quantified using dinitrobenzoic acid. The results showed that ABZ induced ROS accumulation in the ABZ-susceptible Giardia cultures but not in the resistant ones whilst the accumulation of ABZ-SO and ABZ-SOO was lower in all ABZ-resistant cultures. Consistent with these findings, all the antioxidant enzymes detected and analyzed were upregulated in ABZ-resistant clones. Likewise the R-SH pool increased concomitantly to the degree of ABZ-resistance. These results indicate an association between accumulation of ABZ metabolites and a pro-oxidant effect of ABZ in Giardia-susceptible clones. Furthermore the antioxidant response involving ROS-metabolizing enzymes and intracellular free thiols in ABZ-resistant parasites suggest that this response may contribute to overcome the pro-oxidant cytotoxicity of ABZ.